Who has the cure? Hamilton Project ideas on health care - Furman, Jason; Hamilton Project; ProQuest (Firm) (Washington, D.C. : Brookings Institution Press, 2008)
"Emphasizes the importance of universal health care and looks at alternatives for achieving universal health care coverage that also improves efficiency in the health care industry and provides proposals to improve the effectiveness and affordability of health care, including income-related cost-sharing, expanding preventive care, and reforming Medicare's prescription drug benefit"--Provided by publisher.
Universal, effective, and affordable health insurance : an economic imperative / Jason Furman and Robert E. Rubin -- Achieving universal coverage through Medicare part E(veryone) / Gerard F. Anderson and Hugh R. Waters -- Evolving beyond traditional employer-sponsored health insurance / Stuart M. Butler -- A comprehensive cure : the guaranteed health care access plan : a voucher-style reform / Ezekiel J. Emanuel and Victor R. Fuchs -- Taking Massachusetts national : incremental universalism for the United States / Jonathan Gruber -- Mending the Medicare prescription drug benefit : improving consumer choices and restructuring purchasing / Richard G. Frank and Joseph P. Newhouse -- The promise of progressive cost consciousness in health care reform / Jason Furman -- A wellness trust to prioritize disease prevention / Jeanne M. Lambrew.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Right to health -- United States; Health services accessibility -- United States; Health insurance -- United States; National health insurance -- United States; Health care reform -- United States; Electronic books